Final Energy Consumption Trends and Drivers in Czech Republic and Latvia - Zhiqian Yu; Dalia Streimikiene; Tomas Balezentis; Rimantas Dapkus (Amfiteatru Economic Journal, 2017)
This paper analyses the trends of final energy consumption in Latvia and Czech Republic. Analysis of final energy consumption during 2000-2013 period indicated the main driving forces of final energy consumption during and after world financial crisis of 2008. The paper aimed to evaluate the impact of economic activity and other factors on final energy consumption. The decomposition of the final energy consumption is assessed by analyzing effect of different drivers by the main end-users sector (industry, transport, households, agriculture, services), activity, demography, lifestyles, structural effects, energy savings etc. The results show that the reduction in final energy consumption in most EU memb ers states before and after year 2008 can be related to the decline in energy intensities within end - users sectors. At the same time, the increase in final energy intensity after the year 2008 is attributed to expansion of energy demand sectors. Comparison of final energy consumption trends and drivers in Latvia and Czech Republic indicated that Czech Republic implemented more policies and measures in industry and tertiary sector and this provided for final energy consumption decreased and huge energy savings in these sectors.
Keywords: Q4; Q5; Q46; Q48; 330; energy intensity; energy savings; decomposition analysis; Czech Republic; Latvia